Labour and the “Real” Constitution - Arthurs, Harry (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 2007)
While Canada’s formal constitution does not mention labour or employment law, and while jurisprudence has long established the primacy of provincial jurisdiction in this field, labour’s constitutional rights have been the subject of extensive recent litigation and scholarship. This article reviews attempts to use the provisions of the Canadian Charter of Rights and Freedoms to protect labour’s interests and to advance the cause of equality in the workplace. It then explores how Canada’s constitutional architecture has tended to frustrate the interests of unions and workers. And finally, it proposes that labour’s interests will largely be determined not by the formal constitution but by the “real constitution” — the structure of its economy. While the “real constitution” generally disfavours labour’s rights and interests, like the formal constitution it is vague and leaves ample room for challenge and for change.